Post-traumatic biloma intrahepatic a rare complication of closed abdominal trauma: A case report - Daouda Diarra, MD; Siham Salam, Pr; Abdoulfatihi Salihou, MD; Boubacar Traore, PharmD, MPH; Dalale Laoudiyi, Pr; Kamilia Chbani, Pr; Lahcen EL Ouzidane, Pr (Radiology Case Reports, 2022)
Post-traumatic hepatic biloma is a rare complication of closed trauma of the abdomen. Generally, biloma occurs spontaneously or secondary to traumatic or iatrogenic injury to the biliary system. It can lead to significant morbidity and mortality if not diagnosed promptly and properly managed. A 4-year-old child was admitted to the emergency room with abdominal pain following a traffic accident. Clinical examinations suspected closed abdominal trauma without biological signs of icteric cholestasis. Abdominal CT scan performed within 24 hours showed a focus of hepatic laceration, and follow-up imaging at 5 days showed post-traumatic intrahepatic cystic formations. This case report aims to emphasize the importance of imaging including ultrasound, CT, MRI, MRI cholangiopancreatography (MRCP), or hepatobiliary cholescintigraphy to establish the diagnosis and guide the therapeutic gestures.